ULASAN PENERAPAN KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN - Anugrah, Pahrizah Puji; Assidiq, Fuad Mahfud (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2022)
Occupational Health and Safety at the shipyard, is very important for workers, especially at PT IKI during the shipbuilding process. These results have determined the level of risk affecting the shipbuilding process at PT IKI. This research is divided into two stages, the first is to identify the causes of work accidents that often occur in construction activities and the second is to identify how the implementation of the Occupational Safety and Health system at PT IKI. The purpose of this study was to determine the application of Occupational Health and Safety at PT.IKI and to determine the risks during the shipbuilding process at the shipyard. The data used is a literature study through several references related to journals, books and online media. The results of this study indicate that the K3 Party from PT. IKI itself has recorded every accident that occurs in the company and has controlled work accidents that occur. However, there are still some shortcomings such as inadequate fire extinguishers provided, OHS facilities such as statistical information on work accidents, and OHS signs found in the company are still lacking and not maintained and the lack of awareness of workers in complying with the applied OHS regulations.